Canada's military justice system is in a meltdown: will government act? - Drapeau, Michel W.; Létourneau, Gilles; Juneau, Joshua M.; Bédard, Stéfanie (Michel Drapeau Law Office, 2021)
"Cognizant of the growing and persistent systemic flaws found in the military justice system as exposed by several official reports, as well as the cultural issues plaguing our military as recently reported by Canadian media, we are convinced of the urgent need to reinforce its trustworthiness, independence, and fairness. Recently, the military has faced an unprecedented crumbling of the organization as we know it, and the deep-rooted, systemic issues within the Canadian Armed Forces [CAF] are starting to be exposed to the civilian world."--Website